Deoxy-sugar releasing biodegradable hydrogels promote angiogenesis and stimulate wound healing. (December 2017) - Yar, Muhammad; Shahzadi, Lubna; Mehmood, Azra; Raheem, Muhammad Imran; Román, Sabiniano; Chaudhry, Aqif Anwar; ur Rehman, Ihtesham; Ian Douglas, C.W.; MacNeil, Sheila
Graphical abstract: Highlights: Three D-deoxy sugars were explored for their ability to stimulate angiogenesis. L and D isomers were loaded into a chitosan/collagen freeze gelated hydrogel. L-sugars of deoxy ribose, fucose and rhamnose and the D-isomer of 2-deoxy-ribose were pro-angiogenic. L and D isomers of deoxy sugars could not be metabolised by Staphlococcus aureus . A hydrogel containing 2-deoxy D ribose accelerated vascularisation and wound healing in rats. Abstract: Vascular endothelial growth factor (VEGF) stimulates endothelial cells to migrate, proliferate and form new blood vessels. However direct delivery of VEGF has not become clinically adopted as a means of stimulating blood vessel formation and wound healing because of its relatively poor stability and its production of immature blood vessels. A simpler way of stimulating production of VEGF in situ is explored in this study following reports of deoxy sugars involved in inducing VEGF production. The pro-angiogenic effect of L and D isomers of deoxy sugars (ribose, fucose and rhamnose) loaded into biodegradable chitosan/collagen hydrogels was examined using a chick chorionic allantoic membrane assay. The L-sugars were all pro-angiogenic but only the 2-deoxy-d -ribose had strong effects on angiogenesis. Furthermore, these sugars could not be metabolised by four strains of Staphylococcus aureus, as a metabolic substrate for growth, although some of these could be metabolised by another typical pathogen, Pseudomonas aeruginosa . The effects of 2-deoxy-d -ribose in a chitosan/collagen hydrogel on wound healing were also assessed. This biomaterial doubled the rate of cutaneous wound healing in rats associated with an increase in vascularisation detected by staining for CD34 positive cells.